Effect of different ankle braces on lower extremity kinematics and kinetics following special-induced fatigue for volleyball players with functional ankle instability - Zeyi Zhang; Meizhen Zhang (Heliyon, 2023)
Background: The aim of this study is to examine the effects of different ankle braces on functional ankle instability (FAI) participants following special-induced fatigue, which will provide advice for preventing ankle sprains in volleyball game. Methods: A total of 18 male collegiate volleyball players with FAI were recruited. The kinematics and kinetics data were acquired from the participants during single-leg drop landing using the infrared motion capture system (Mars2H, Nokov, China) and the force platform (Bertec, USA). A 2 × 2 within subjects design ANOVA was adopted to analyze the data. Results: Whether fatigue or not, soft and semi-rigid brace reduced the ankle inversion (P = 0.025). Moreover, soft brace reduced the sagittal range of motion (ROM) of the ankle joint before fatigue (P = 0.05). In addition, the semi-rigid brace shortened the time to stability in the medial and lateral directions (P = 0.039) as well as the vertical directions (P < 0.001). The semi-rigid brace reduced the ground reaction force post-fatigue (P = 0.001). Conclusion: Soft ankle brace reduced the sagittal range of motion pre-fatigue. Since volleyball requires athletes to jumping and landing repeatedly, and the ankle sagittal ROM was an important cushion during landings. Thus, soft ankle brace might result in overuse injury for lower extremity. However, the semi-rigid ankle brace increased the dynamic stability in the medial and vertical directions, and reduced the ankle inversion angle and forward ground reaction force post-fatigue. This ensured that the volleyball player's ankle was in a neutral position during landing, reducing the risk of excessive inversion caused by contact with the opposing player during spike and block.